Development of polymer composites using modified, high-structural integrity graphene platelets - Jun, Ma; Meng, Qingshi; Zaman, Izzuddin; Zhu, Shenmin; Michelmore, Andrew; Nobuyuki, Kawashima; Wang, Chun H.; Kuan, Hsu-Chiang (Elsevier, 2014)
Previous studies on polymer/graphene composites have mainly utilized either reduced graphene oxide or graphite nanoplatelets of over 10 nm in thickness. In this study we covalently modified 3-nm thick graphene platelets (GnPs) by the reaction between the GnPs’ epoxide groups and the end-amine groups of a commercial long-chain surfactant (Mw = 2000), compounded the modified GnPs (m-GnPs) with a model polymer epoxy, and investigated the structure and properties of both m-GnPs and their epoxy composites. A low Raman ID/IG ratio of 0.13 was found for m-GnPs corresponding to high structural integ- rity. A percolation threshold of electrical conductivity was observed at 0.32 vol% m-GnPs, and the 0.98 vol% m-GnPs improved the Young’s modulus, fracture energy release rate and glass transition tem- perature of epoxy by 14%, 387% and 13%, respectively. These significantly improved properties are cred- ited to: (i) the low Raman ID/IG ratio of GnPs, maximizing the structural integrity and thus conductivity, stiffness and strength inherited from its sister graphene, (ii) the low thickness of GnPs, minimizing the damaging effect of the poor through-plane mechanical properties and electrical conductivity of graphene, (iii) the high-molecular weight surfactant, leading to uniformly dispersed GnPs in the matrix, and (iv) a covalently bonded interface between m-GnPs and matrix, more effectively transferring load/electron across interface.